"Resistance is Possible": The Ethnography of Roleplaying. Issue 1 (27th January 2020) - LEBLANC, NATHAN
Abstract : Roleplaying games, such as the popular Dungeons & Dragons, ask players to take on roles of particular people and contexts. As a researcher, my experience conducting playtesting and ethnographic work for a roleplaying game on the Holocaust called "Rosenstrasse" profoundly affected me. In this PechaKucha, I ponder how roleplaying games might inspire the communication of ethnographic insight. As a medium in which storytelling isn't linear or prescribed, how can roleplaying games effectively transfer cultural understanding? Just as a Games Master and game design facilitate this knowledge transfer, perhaps ethnographers can use techniques similar to roleplaying to increase change‐making by enabling greater agency in stakeholders and teammates.